Superselective transarterial radioembolization for the treatment of hepatocellular carcinoma - Gyoung Min Kim (Society of Gastrointestinal Intervention, 2021)
Superselective transarterial radioembolization (TARE) refers the delivery of Y90 at the tumor-feeding segmental or subsegmental arteries. The purpose of TARE would be delivering high dose in the tumor while saving as much normal parenchyma as possible. This concept is similar to the radiation segmentectomy. To identify all tumor feeders, thorough angiography and cone-beam computed tomography are essential. Reported target dose of radiation segmentectomy ranges 222.6-521 Gy. After superselective TARE, the treated segments can show persistent enhancement, and then atrophy combined with capsular retraction. Superselective TARE promises favorable outcomes. It's reported objective response rates range 64%-95% and toxicities are tolerable in most cases. In conclusion, superselective TARE is a very safe modality for the treatment of HCCs with favorable outcome close to the curative-intent treatments in selected patients.